The cross-cultural adaptation and psychometric evaluation of a Chinese version of the postoperative symptom severity (PoSSe) scale - Xiang Li; Zefan Niu; Chen Gao; Annika Kroeger; Georgios Tsakos; Bolong Li; Jiaqi Zhu; Gang Chen; Thomas Dietrich (BDJ Open)
Abstract Background The postoperative symptom severity (PoSSe) scale, which was developed in the UK, measures the impact of postoperative morbidity on patients’ quality of life after lower third molar surgery. It has recently been used in Chinese populations but without having been adapted and validated for these populations. The aim of this study was to cross-culturally adapt and psychometrically evaluate a Chinese version (Simplified Chinese) of the PoSSe scale for applications in third molar surgery in Chinese patient populations. Methods We employed a rigorous multi-step cross-cultural adaptation process, including forward and backward translation followed by pilot testing, where participants documented the relevance and ease of understanding of the PoSSe items. The psychometric evaluation of the final Chinese version took place in a sample of 101 patients undergoing lower third molar surgery in Tianjin, China. Cronbach’s Alpha (α) coefficient was calculated for the reliability evaluation, while the Spearman correlation coefficient (r s ) and Pearson’s correlation coefficient (r) were used for validity assessment. Results The PoSSe scale demonstrated excellent internal consistency (Cronbach’s α = 0.80 for the whole sample; α = 0.80 among patients with bone removal during surgery; α = 0.81 among patients without bone removal during surgery). For validity assessment, PoSSe scores had statistically significant associations with the extent of surgical trauma (osteotomy and duration of surgery), self-reported pain and clinically assessed trismus. The strength of these associations varied between the two groups (with and without bone removal during surgery) in the expected direction. The results suggest that the Chinese version of the PoSSe scale has acceptable linguistic clarity, cultural relevance, and context appropriateness, showing excellent internal consistency and validity and can be confidently used for clinical and research applications in Chinese patient populations. Conclusions The PoSSe scale has been successfully cross-culturally adapted for postoperative use among Chinese patients undergoing third molar surgery and demonstrated successful psychometric assessment for its reliability and validity, which allows future informative studies in China, also in terms of comparison across countries involving China that could assess the cultural equivalence of the measure.